BIODEGRADASI MINYAK OLEH Rhodotorula dan Candida HASIL ISOLASI DARI PELABUHAN TANJUNG PERAK SURABAYA - Tri Nurhariyati; Ni’matuzahroh Ni’matuzahroh; Tini Surtiningsih (The East Java Biological Society, 2006)
A research about isolation and capability of isolat yeast from Tanjung Perak Harbor, Surabaya in degrading kerosen, gas oil ,and lubricant were conducted. This research were done to know the influence of Rhodotorula, Candida and Mix of Rhodotorula and Candida; the influence of oil type and interaction of both (between yeast and oil) in decreasing oil weight. Research design was laboratory experimental and using the factorial 4 × 3 with five replication. The data were analyzed by two-way ANOVA (p: 0.05) and followed by t test. The result of the biodegradation test showed that the kind of yeast, the kind of oil weight and interaction of both influence in decreasing of oil weight. The most decreasing of oil weight obtained by mix of Rhodotorula and Candida (82.55%), kerosen (66.59%) and combination mix of yeast (Rhodotorula and Candida) and kerosen (89.32%).